2011
DOI: 10.1159/000323457
|View full text |Cite
|
Sign up to set email alerts
|

The Progressive Ankylosis Protein Regulates Cementum Apposition and Extracellular Matrix Composition

Abstract: Background/Aims: Tooth root cementum is sensitive to modulation of inorganic pyrophosphate (PPi), an inhibitor of hydroxyapatite precipitation. Factors increasing PPi include progressive ankylosis protein (ANK) and ectonucleotide pyrophosphatase/phosphodiesterase 1 (NPP1) while tissue nonspecific alkaline phosphatase hydrolyzes PPi. Studies here aimed to define the role of ANK in root and cementum by analyzing tooth development in Ank knock-out (KO) mice versus wild type. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 176 publications
8
73
1
Order By: Relevance
“…Intramembranous bone forms as a two-step process whereby osteoblasts secrete the ECM (osteoid), and then in a second step, the matrix becomes mineralized in a regulated process. In contrast, acellular cementum formation involves a directed mineralization of the collagen fringe fibers at the tooth root surface (Bosshardt and Schroeder, 1991), a process that we and others have found to be heavily reliant on the physicochemical process of mineralization (Beertsen et al, 1985; Beertsen et al, 1999; Foster et al, 2011; Foster et al, 2012; Jayawardena et al, 2002; Kaipatur et al, 2008; McKee et al, 2011; Nociti et al, 2002; Zweifler et al, 2014). With lack of BSP, craniofacial intramembranous bone is delayed in the conversion from osteoid to mineralized bone.…”
Section: Discussionmentioning
confidence: 86%
“…Intramembranous bone forms as a two-step process whereby osteoblasts secrete the ECM (osteoid), and then in a second step, the matrix becomes mineralized in a regulated process. In contrast, acellular cementum formation involves a directed mineralization of the collagen fringe fibers at the tooth root surface (Bosshardt and Schroeder, 1991), a process that we and others have found to be heavily reliant on the physicochemical process of mineralization (Beertsen et al, 1985; Beertsen et al, 1999; Foster et al, 2011; Foster et al, 2012; Jayawardena et al, 2002; Kaipatur et al, 2008; McKee et al, 2011; Nociti et al, 2002; Zweifler et al, 2014). With lack of BSP, craniofacial intramembranous bone is delayed in the conversion from osteoid to mineralized bone.…”
Section: Discussionmentioning
confidence: 86%
“…Alpl -/-mice harbor increased levels of the mineral inhibitor pyrophosphate (PP i ) and serve as a model of hypophosphatasia (HPP), where lack of acellular cementum predisposes to tooth loss (van den Bos et al, 2005). We have demonstrated that reduction of PP i , in turn, promotes increased acellular cementum formation (Foster et al, 2011, and hypothesized that acellular cementum represents a tissue strongly regulated at the physicochemical level of mineralization, i.e., hydroxyapatite nucleation and growth. Cellular cementum size was undiminished by the loss of BSP, though mineralization was delayed at earlier ages; functional consequences of this are under study.…”
Section: Acellular Cementum As a Mineralization-sensitive Tissuementioning
confidence: 99%
“…Cementum and bone share regulatory pathways and key developmental influences as evidenced by mouse genetic studies and human disease phenotypes [24]. However, accumulated evidence over the past two decades has revealed that acellular cementum is hypersensitive to regulators of mineralization, apparently more so than other hard tissues of the dentition and skeleton [57]. …”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking either ANK or ENPP1 activity ( Ank −/− and Enpp1 −/− mice, respectively) feature decreased extracellular PP i production/secretion and are predisposed to ectopic calcification [17, 19, 22, 23]. In the absence of ANK or ENPP1, acellular cementum is dramatically increased, pointing to PP i as a central regulator tuning cementum growth and mineralization [57]. Additional examples of the sensitivity of acellular cementum to disturbances in mineralization come from studies of endocrine disorders like X-linked hypophosphatemia (XLH; OMIM 307800) [24, 25] and autosomal recessive hypophosphatemic rickets (ARHR; OMIM 241520) [26], transgenic mouse models over-expressing mineralization inhibitors like matrix gla protein [27], or administration of pharmacologic agents such as etidronate, a synthetic PP i analog [2830], where acellular cementum formation and function are negatively affected.…”
Section: Introductionmentioning
confidence: 99%